PENGARUH NILAI TAKSIRAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN NASABAH DALAM MELAKUKAN GADAI EMAS DI PEGADAIAN UPC TULADENGI - Sari, Ely Nurmay (Program Studi Akuntansi, 2023)
This study aims to determine the effect of the estimated value and service quality simultaneously on the customer's decision to pawn gold at Pegadaian UPC Tuladengi partial or simultaneous. This research is a quantitative research. Population in Research of 113 customers then the sampling method is purposive sampling So that the sample in the study was 38 people. The results of this study show that The estimated value and quality of service partially or simultaneously have a significant effect on the customer's decision to pawn gold at Pegadaian UPC Tuladengi. The Ajusted R Square value is 0.240. This value shows that 24% of the variability in customer decision accountability in pawning gold at UPC Tuladengi Pawnshop is explained by the estimated value and service quality, while the remaining 74% can be explained by other variables that were not studied in this study.